2016
DOI: 10.1128/mcb.00053-16
|View full text |Cite
|
Sign up to set email alerts
|

Occludin S471 Phosphorylation Contributes to Epithelial Monolayer Maturation

Abstract: Multiple organ systems require epithelial barriers for normal function, and barrier loss is a hallmark of diseases ranging from inflammation to epithelial cancers. However, the molecular processes regulating epithelial barrier maturation are not fully elucidated. After contact, epithelial cells undergo size-reductive proliferation and differentiate, creating a dense, highly ordered monolayer with high resistance barriers. We provide evidence that the tight junction protein occludin contributes to the regulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 60 publications
0
19
0
Order By: Relevance
“…It has been found that MDCK epithelial cells undergo post-contact proliferation necessary for proper epithelial maturation and tight junction formation. Inhibition of occludin Ser471 phosphorylation by either an alanine mutation or inhibition of the G-protein regulated kinase that targets this site, prevents this epithelial maturation and blocks tight junction formation with no effect on adherens junction formation (Bolinger, Ramshekar et al 2016). Together these data show the complex role of occludin in barrier regulation, cell growth, angiogenesis, and permeability transport regulation.…”
Section: Flux Across the Ibrbmentioning
confidence: 99%
“…It has been found that MDCK epithelial cells undergo post-contact proliferation necessary for proper epithelial maturation and tight junction formation. Inhibition of occludin Ser471 phosphorylation by either an alanine mutation or inhibition of the G-protein regulated kinase that targets this site, prevents this epithelial maturation and blocks tight junction formation with no effect on adherens junction formation (Bolinger, Ramshekar et al 2016). Together these data show the complex role of occludin in barrier regulation, cell growth, angiogenesis, and permeability transport regulation.…”
Section: Flux Across the Ibrbmentioning
confidence: 99%
“…89 In a more recent study, they demonstrated that over-expression of ocln S471A blocked monolayer maturation and normal tight junction protein localization, consistent with a requirement for phosphorylation at this site in meditating normal interactions with ZO-1 and cell packing. 81 In addition to these phosphorylation sites, Dorfel and Huber 90 identified a phosphorylation hotspot within the ocln c-terminal domain, an 11 amino acid stretch from 398-408. Within this region, Raleigh et al 91 had found that inhibition of CK2-mediated Figure 3.…”
Section: Tamp Family Phosphorylationmentioning
confidence: 99%
“…2 The occludin C-terminal coiled-coil domain binds directly to zonula occludens-1 (ZO-1) 3 via interactions regulated by phosphorylation within and adjacent to that region. [4][5][6][7] A range of in vitro studies, including analyses of peptides corresponding to occludin domains, 8 occludin knockdown, [9][10][11] or expression of occludin mutants (eg, those lacking the C-terminal tail), 12 suggest that occludin limits paracellular permeability to macromolecules. The observation that occludin removal from the tight junction, either in response to F-actin depolymerization or cytokine stimulation, 10,13,14 increases leak pathway permeability is consistent with this function.…”
mentioning
confidence: 99%